Paediatric's first aid (epistaxis : hidung berdarah) - Muhd Helmi, Muhd Alwi; Anuar, Muhamad Azamin; Mohamad Khairi, Siti Nur Lina; Ahmed, Ebrahim Adel Ali (2021)
Training kit for nursery and kindergarten teachers on how to assess and treat epistaxis children.